Polskie przekłady „Testamentum porcelli” - Pieczonka, Joanna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The purpose of the article is to analyse the four Polish translations of Testamentum porcelli: by Witold Truszkowski (1972), Magdalena Nowak (1996), Maciej Jońca (2011) and the team comprising Andrzej Dzikowski, Aldona Jurewicz and Gabriela Molisak (2016). Every translator has their own strategy for rendering the text in Polish but none of them includes all the aspects of the ancient parody: linguistic peculiarities (colloquialisms, neologisms), stylistic figures, technical terminology (zootechnical and legal), the differences in style and humorous tone of the of the text. The translation strategies applied by the translators vary depending on the research field which lies within the scope of interest of each translator. Truszkowski concentrates on proper rendering of the stylistic features of the text, and is especially interested in the colloquial character of the ancient parody. Nowak attempts to focus on the sources of humour, but her translation is nearly literal. Jońca draws attention to technical legal terms, as does the team Dzikowski, Jurewicz and Molisak, although these translators also emphasise zootechnical lexemes. Each of these translation strategies shows a different layer of Testamentum porcelli. Sprostowanie: W prezentowanej w artykule Joanny Pieczonki analizie przekładu "Testamentum porcelli", dokonanego przez Andrzeja Dzikowskiego, Aldonę Jurewicz i Gabrielę Molisak, zawarta została błędna informacja jakoby dr Andrzej Dzikowski był zoologiem, podczas gdy w rzeczywistości jest z wykształcenia prawnikiem i lekarzem weterynarii. Za powyższą pomyłkę serdecznie przepraszamy.